2014
DOI: 10.1038/cddis.2014.101
|View full text |Cite
|
Sign up to set email alerts
|

Opposing TNF-α/IL-1β- and BMP-2-activated MAPK signaling pathways converge on Runx2 to regulate BMP-2-induced osteoblastic differentiation

Abstract: In patients who were treated with exogenous BMP-2 to repair bone fractures or defects, the levels of the inflammatory cytokines such as TNF-α and IL-1β in sera are significantly elevated, which may affect the outcome of bone regeneration. Mitogen-activated protein kinase (MAPK) cascades such as extracellular signal-regulated kinase 1/2 (ERK1/2), p38, and c-Jun NH2-terminal kinase 1/2 (JNK1/2) have a crucial role in osteogenic differentiation and are activated by both BMP-2 and TNF-α/IL-1β. However, previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 61 publications
4
124
3
Order By: Relevance
“…Similarly, it was reported that the BMP2-induced osteoblastic differentiation of MSCs was inhibited by TNF-α through activation of MAPK signaling pathway [19, 44, 45], while other studies suggest that TNF-α inhibited BMP/Smads signaling through the activation of NF-κB signaling pathway[46-48]. Nonetheless, the molecular mechanisms underlying such inhibition remain to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it was reported that the BMP2-induced osteoblastic differentiation of MSCs was inhibited by TNF-α through activation of MAPK signaling pathway [19, 44, 45], while other studies suggest that TNF-α inhibited BMP/Smads signaling through the activation of NF-κB signaling pathway[46-48]. Nonetheless, the molecular mechanisms underlying such inhibition remain to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an earlier study reported that TNF-α and BMP2 had opposing effects on osteoblastic differentiation of C2C12 and MC3T3-E1 cells [19]. While the exact mechanisms need to be understood, it offers a promise that exogenous BMP9 may be used to promote the bone defect repair and bone regeneration in the presence of high doses of TNF-α or under chronic inflammation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that MMP-2 inhibition by siRNA technique resulted in decreased expression of BMP-2, which in turn reduced the levels of Smad signalling protein levels remarkably. BMP molecules induce ligand-dependent type I and type II receptor heterodimerization, which activates p-Smad1/5/8 that bind Smad4 (32). The inhibition of BMP/Smad signalling by siRNA-MMP-2 was also associated with the inhibition of Cbfa-1 expression.…”
Section: Discussionmentioning
confidence: 79%
“…Glucocorticoid serves a crucial regulatory function in the proliferation and differentiation of MSCs (13). Under certain conditions, hormones are able to induce MSC proliferation, differentiation and differentiation direction changes, potentially causing bone necrosis (14). The limited self-repair capacity associated with SANFH may be associated with the limited number and the weak proliferative activity of MSCs in femoral neck and femoral metaphyseal bone marrow of these patients (15).…”
Section: Introductionmentioning
confidence: 99%